Integrating Environmental Considerations in Policy Formulation : Lessons from Policy-Based Strategic Environmental Assessment (SEA) Experience - World Bank (Washington, DC, 2012)
This report reviews the application of the Strategic Environmental Assessment (SEA) to policies and draws lessons from it. The principal conclusion is that current SEA approaches, based on EIA methodology, of the sample reviewed have some influence on policy design but it is difficult to evaluate whether the SEA recommendations that have been incorporated into the policy are the key for sustainability or whether they only affect peripheral issues. Furthermore, beyond the design phase, there is even less information about implementation of these environmental aspects of public policies. This report suggests that the SEA, as an evolving tool, could improve its influence on policymaking by more directly addressing institutional and governance dimensions. Specifically, countries should 1) use both quantitative and participatory techniques, in order to select themes or sectors for which there is a definite recognition of the severity of environmental problems; 2) incorporate mechanisms that bring together different viewpoints, including those most vulnerable to environmental degradation, during the policy formulation and implementation process; 3) ensure social accountability by passing legislation to allow for greater transparency in decisionmaking and outcomes, advocacy through a free press, and strengthening of recourse measures such as the complaints systems or the judiciary; and 4) improve social learning so that key environmental priorities are given attention and continuously brought to the policy agenda.